Hospitalizations due to self-poisoning at a Canadian paediatric hospital. Issue 2 (22nd December 2017) - Chafe, Roger; Aslanova, Rana; Hamud, Omer; Gregory, Peter; Newhook, Leigh Anne
Abstract: Background: Adolescent self-harm by drug ingestion (i.e., self-poisoning) is a serious mental health issue. In Newfoundland and Labrador (NL), paediatricians suspected an increase in the number of adolescents hospitalized due to self-poisoning in the province. Our primary aim was to evaluate the number of hospital admissions of adolescents for self-poisoning between 2008 and 2013 to determine whether there was indeed an increase in hospitalizations. We also wanted to examine the characteristics of these admissions to better understand this patient population. Method: A retrospective chart review was conducted to identify cases of self-poisoning admitted to the only paediatric hospital in NL over a 6-year period. A data abstraction form was developed to collect patient demographic information and details about these incidences of self-poisoning. Results: A total of 156 patient admissions were identified; 97 (62.2%) first time admissions and 59 (37.8%) recurrent admissions. The number of admissions for self-poisoning increased over the study period from 2.1% of total hospital admissions in 2008 to 6.5% in 2013. Mean (SD) age at the time of admission was 15.4 years, 122 patients (78.2%) were female and 86.5% had at least 1 previous mental health diagnosis. The most common drugs ingested were analgesics (38.0%) and antidepressants (32.2%), with 73 patients (48.7%) ingesting multiple drugs. Conclusions: The study contributes to the growing recognition of adolescent self-poisoning as a serious paediatric mental health issue. It also confirmed that an increase in adolescent hospitalizations due to self-poisoning has occurred in NL. Further research is warranted to identify effective prevention strategies for this serious problem.